Electrical and structural properties of heterojunction AZO, NZO and NiO thin films - Dejam, Laya; Ghaderi, Atefeh; Solaymani, Shahram; Sabbaghzadeh, Jamshid; Țălu, Ștefan; Salehi Shayegan, Amir Hossein (Applied physics. A, Materials science & processing, 2023)
Semiconducting metal oxide thin films of ZnO and NiO with different impurity of n-type and p-type conductivity were grown on a Si substrate by magnetic sputtering method. The structural characteristics, i.e. crystalline characteristics and crystalline order or amorphousness of layers, were investigated by X-ray diffraction. The PL spectrum of ZnO samples doped with N and Al had a peak at a wavelength of approximately 370 nm, which is close to band gap energy of ZnO, and the highest intensity was observed in the PL spectrum of AZO sample. The effect of nanoparticle size of grown layers and their effect on performance of joints were investigated. Evaluation of the performance of metal oxide structures with current and voltage diagrams of connections and their applications in electronic devices showed that the smallest ideal diode factor is related to the Si-n/NZO-p connection with a value of 1.23, which showed the best behavior of the diode.